Spleen Wandering and Axial Torsion following Nissen Fundoplication: A Case Report - Shady Fayek; Mazen Elesseily; Heba Taher; Mostafa Rifaat Elmorsy; Youssef Ibrahim Abo Alsoud; Mariam Mohammed Marei; Mohammed Rabeh Moufak Abduldaem; Adrian Park (Pediatric Sciences Journal, 2025)
Wandering spleen and its axial torsion is a very rare entity that presents with abdominal pain. Splenic torsion might be related to the division of the long vascular pedicle of spleen, or to its weight in portal hypertension. Splenic torsion and infarction following Nissen fundoplication is a rare long-term but potentially life-threatening complication. We report the case of a 17-year- old female who presented to emergency room by severe agonizing incapacitating left hypochondrial pain. She had been suffering from indolent abdominal pain for 4 months that alternated with attacks of severe pain, the pain recurred more frequently and increased in intensity during the past week prior to her presentation. There was no vomiting, fever or any other symptoms, and she was vitally stable except for tachycardia. Her medical history was remarkable, with 3 previous surgical interventions. She underwent an appendectomy, an exploratory laparotomy for intestinal obstruction and laparoscopic Nissen fundoplication. A thorough examination of the patient, and computed tomography (CT) scan of her abdomen showed torsion of the spleen. Exploratory laparotomy, revealed a midline positioned spleen of dusky discoloration. Repositioning did not achieve improvement in spleen color and splenectomy were performed. The patient was discharged without any incidents or complications. Splenic torsion is a rare complication of Nissen fundoplication surgery, that is life-threatening. A high index of suspicion is necessary for diagnosis. While exploratory laparotomy is the golden diagnostic standard, Doppler of splenic vein and CT abdomen are valuable. The indolent pain alternating with episodic more severe nature of the pain might be related to the rate and direction of splenic vessels axial torsion (twisting and untwisting), i.e. rate of partial compression and relief of compression of the blood flow in the long vascular pedicle of spleen until it reaches complete torsion and complete obstruction. Early diagnosis is essential to prevent splenic infarction and morbidity. Exploratory laparotomy was lifesaving in our reported case.